Agrobacterium rhizogenes mediated genetic transformation resulting in hairy root formation is enhanced by ultrasonication and acetosyringone treatment - Kumar, Vinod; Sharma, Ashwani; Prasad, Bellur Chayapathy Narasimha; Gururaj, Harishchandra Bhaskar; Ravishankar, Gokare Aswathanarayana (Electronic Journal of Biotechnology, 2006)
The phytopathogenic bacteria Agrobacterium rhizogenes genetically transforms plants by transferring a portion of the resident Ri plasmid, the T-DNA to the plant. Plant species differ in their temporal competence for transformation. But various physical and chemical methods are found to enhance transformation frequency. Agrobacterium rhizogenes mediated transformation efficiency was assessed under the influence of sonication, calcium treatment, acetosyringone and macerating enzymes in suitable combinations in Nicotiana tabacum as a model system. Manual wounding resulted in 21% transformation frequency. Where as sonication resulted in 2.2 fold increase, followed by sonication with CaCl2 treatment resulted in 2.5 fold increase and sonication with acetosyringone treatment resulted in 4.1 fold increase in transformation frequency. However, sonication with macerating enzyme treatment resulted in 1.5 to 5.25-fold decrease in transformation frequency. Micro wounding through sonication followed by acetosyringone treatment enhanced transformation frequency substantially. The results of this study may be very useful in genetic manipulation of plants by Agrobacterium rhizogenes mediated gene delivery to higher plants, which are recalcitrant to A. tumefaciens mediated genetic manipulation.